2014
DOI: 10.2147/dddt.s63320
|View full text |Cite
|
Sign up to set email alerts
|

Topical infliximab for the suppression of wound healing following experimental glaucoma filtration surgery

Abstract: BackgroundThe purpose of this work was to look into the effects of infliximab on wound healing in experimental glaucoma filtration surgery and to compare the antifibrotic effects of this agent to that of mitomycin-C (MMC).MethodsTwenty-eight male New Zealand White rabbits were randomly assigned to four groups, each including seven rabbits: control group, sham group, MMC group, and infliximab group. The rabbits in the control group were not operated on and did not receive any treatment. The rabbits in the sham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
9
0
3
Order By: Relevance
“…Several studies reported that these factors are potent stimulators of HTF proliferation in vitro (Cunliffe et al, 1995;Denk et al, 2003;Knorr et al, 1997). Furthermore, inhibition of some of these molecules diminished growth of cultured human TF (Salas-Prato et al, 1996) and improved glaucoma filtration surgery outcome in an experimental glaucoma model (Turgut et al, 2014). However, none of these factors have reached the stage of a clinical trial.…”
Section: Other Growth Factors and Cytokinesmentioning
confidence: 99%
“…Several studies reported that these factors are potent stimulators of HTF proliferation in vitro (Cunliffe et al, 1995;Denk et al, 2003;Knorr et al, 1997). Furthermore, inhibition of some of these molecules diminished growth of cultured human TF (Salas-Prato et al, 1996) and improved glaucoma filtration surgery outcome in an experimental glaucoma model (Turgut et al, 2014). However, none of these factors have reached the stage of a clinical trial.…”
Section: Other Growth Factors and Cytokinesmentioning
confidence: 99%
“…Our retrospective design cannot address cause and effect, but previous studies [21][22][23] support the interpretation that systemic TNF inhibitors used at the time of the MMC-augmented trabeculectomy may have protected patients against scarring of the trabeculectomy bleb. …”
Section: Discussionmentioning
confidence: 85%
“…В условиях in vitro эти фак-торы являются мощными стимуляторами пролифера-ции фибробластов теноновой капсулы человека [38]. По-давление активности некоторых из этих молекул также препятствует росту этих клеток в культуре и улучшает исходы экспериментальной хирургии глаукомы [39]. Впрочем, клинические испытания в этом направлении не проводились.…”
Section: другие факторы роста и цитокиныunclassified